2011
DOI: 10.1007/s10337-011-2059-6
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of C-Phycocyanin in the Presence of Cells Using Expanded Bed IEC

Abstract: C-Phycocyanin is a natural blue dye that can be extracted from Spirulina platensis. In this paper, a crude extract of C-phycocyanin in the presence of cells was purified using ion exchange chromatography in an expanded bed. The elution was studied aiming at its optimization using a central composite rotatable design (CCRD), the independent variables being the pH and elution volume, and the responses purity, concentration, yield and recovery. An evaluation of the contour curves showed that the best conditions f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…The Streamline DEAE has been used in C‐phycocyanin purification with an expanded bed; however, most reports mention clarified extract . Supports, such as Q XL, have only recently been used since few authors have reported their uses …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Streamline DEAE has been used in C‐phycocyanin purification with an expanded bed; however, most reports mention clarified extract . Supports, such as Q XL, have only recently been used since few authors have reported their uses …”
Section: Resultsmentioning
confidence: 99%
“…[26][27][28] Supports, such as Q XL, have only recently been used since few authors have reported their uses. [20,21] Employing unclarified extracts in EBC processes without dilution usually causes flow disturbance and unequal sample distribution due to its high viscosity. [2] We too had observed this fact, which causes a collapse in the expanded bed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a typical cycle of purification by EBA chromatography including equilibration (30 min), loading (30 min), washing (60 min) and elution (30 min) only took 2.5-3.5 h, making the process attractive for large-scale use [43].…”
Section: Direct Purification Of the 503 Antigen From Unclarified Feedmentioning
confidence: 99%
“…No studies were found that determined the isotherms on a Q XL matrix, except for one that studied the use of this matrix for the adsorption of C-phycocyanin by EBIEC from a crude extract in the presence of cells (Moraes et al, 2011a).…”
Section: Adsorption Isothermmentioning
confidence: 99%